2019
DOI: 10.3390/pharmaceutics11120683
|View full text |Cite
|
Sign up to set email alerts
|

Combined Modality Therapy Based on Hybrid Gold Nanostars Coated with Temperature Sensitive Liposomes to Overcome Paclitaxel-Resistance in Hepatic Carcinoma

Abstract: In this study, we prepared gold nanostar (GNS) composite nanoparticles containing siRNA of cyclooxygenase-2(siCOX-2) that were modified by tumor targeting ligand 2-deoxyglucose (DG) and transmembrane peptide 9-poly-D-arginine (9R) to form siCOX-2(9R/DG-GNS). Paclitaxel loaded temperature sensitive liposomes (PTX-TSL) were surface-modified to produce PTX-TSL-siCOX-2(9R/DG-GNS) displaying homogeneous star-shaped structures of suitable size (293.93 nm ± 3.21) and zeta potentials (2.47 mV ± 0.22). PTX-TSL-siCOX-2(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…For example, Guo and co‐workers prepared a gold nanostar (GNS), followed by complexing it with therapeutic siRNA. [ 361 ] Sequentially, the resulting siRNA/GNS complexes were loaded into a Ptx‐containing thermo‐sensitive liposomes. With such a hybridized carrier design, the resulting hybrids showed capabilities of intracellular rapid release of the loading payload, enhanced uptake by tumor cells and overcoming MDR in cancer cells.…”
Section: Therapeutic Modalities For Combating Cancer Via O/i Hybridsmentioning
confidence: 99%
“…For example, Guo and co‐workers prepared a gold nanostar (GNS), followed by complexing it with therapeutic siRNA. [ 361 ] Sequentially, the resulting siRNA/GNS complexes were loaded into a Ptx‐containing thermo‐sensitive liposomes. With such a hybridized carrier design, the resulting hybrids showed capabilities of intracellular rapid release of the loading payload, enhanced uptake by tumor cells and overcoming MDR in cancer cells.…”
Section: Therapeutic Modalities For Combating Cancer Via O/i Hybridsmentioning
confidence: 99%
“…Then, 0.5 mL of the release sample was taken out and replaced with an equal volume of fresh release medium at predetermined intervals. 19 , 33 The content of siRNA in the samples was determined by spectrofluorometer, and the cumulative release of siRNA was calculated according to Equation (2) : where V is the volume of release medium, C t represents the determined concentration of siRNA in the collected samples at time t, ∑C m denotes the concentration sum of the collected samples, V r corresponds to the volume of samples removed for analysis, and Dose is the amount of siRNA added into the release medium.…”
Section: Methodsmentioning
confidence: 99%
“…The NIR-responsive liposomes were established by incorporating AuNSs with a diameter of 45-50 nm into the aqueous core of liposomes, which allows the conversion of NIR-light energy to heat energy to con-trol the drug release [99]. Another report developed a PTX-TSL-AuNS co-delivery system, which has the advantages of rapid PTX release and easy intracellular uptake under hyperthermia [100]. The encapsulation efficiency and drug loading of PTX are about 92.3% and 7.2%, respectively, suggesting a feasible method for PTX delivery.…”
Section: Preparation Methods and Encapsulation Strategy Of Nirn-lipsmentioning
confidence: 99%
“…The encapsulation efficiency and drug loading of PTX are about 92.3% and 7.2%, respectively, suggesting a feasible method for PTX delivery. This co-delivery system exhibits high stability for minimal changes in size and PDI during three weeks at 4 • C [100]. Studies have found that the binding of AuNPs on liposomes' surface easily generated liposomes aggregation and drug leakage [101].…”
Section: Preparation Methods and Encapsulation Strategy Of Nirn-lipsmentioning
confidence: 99%